Conceptualization of Culture and Ethnicity within Social Work in Two Indigenous Communities: Implications for Culturally Adequate Social Work (Journal of Comparative Social Work, 2018)
This qualitative study compares social work in Sami communities within Norway and Native American communities in Montana in the US. A total of 39 social workers were interviewed. We investigated the conceptualization of culture and ethnicity, as well as the implications of these constructions for a culturally adequate social work practice. We find that social workers in Sápmi conceptualize culture and ethnicity as hybrid and fluid, while the social workers in Native American communities have a more fixed and static conceptualization. When working in Native American communities, social workers’ theme of inequality among groups, and the continuing effect of assimilation on family life. Among social workers in Sami communities in Norway, little attention is given to power relations among ethnic groups. These differences in construction affect both the framing and the legitimacy of culturally adequate social work within these two contexts.